Investment and Union Certification - Fallick, Bruce C.; Hassett, Kevin A. (Journal of Labor Economics, 1999)
Using data on union certification elections, we estimate the impact of unionization on firms' investment behavior. Employing both a standard q model and an “investment surprises” technique, we find that union certification significantly reduces investment in the year following the election. We find that a winning certification election has, on average, about the same effect on investment in the year following the event as would—given the elasticity measures taken from the public finance literature—a 33 percentage‐point increase in the corporate tax. The magnitude of the response in years further away from the election is less certain.